The Effectiveness of Learning to Write Explanation through a Scientific Approach Using Project-Based Learning - Yusmaniar Yusmaniar; Rochmat Tri Sudrajat; Ika Mustika (Budapest International Research and Critics University, 2022)
The purpose of this study was to see how the effectiveness of project-based learning with a scientific approach was able to improve students' ability to write explanatory texts. This study uses a quasi-experimental method by using a research design in the form of Nonequivalent Control Group Design. The samples used were two classes, namely class XI MIPA 1 as an experimental class with 36 students receiving project-based learning treatment and class X MIPA 2 as a control class with 36 students receiving problem-based learning treatment. The results of the explanatory text writing test based on observations showed data that project-based learning was more effective in improving students' explanatory text writing skills, this was also reinforced by the data from observations that showed that 95% of students were more motivated to improve their explanatory text writing skills when using project-based learning